Thermal stability and slip effects in micropolar nanofluid flow over a shrinking surface: A numerical study via Keller box scheme with block-elimination method - Tasawar Abbas; Sami Ullah Khan; Munazza Saeed; M. Ijaz Khan; Emad A. A. Ismail; Fuad A. Awwad; Barno Sayfutdinovna Abdullaeva (AIP Advances, 2024)
The slip flow of nanofluids has engaged potential applications in different engineering processes, including oil recovery, aerodynamics, microfluidic and chip devices, lubrication and tribology, and environmental engineering. Following such motivated applications in mind, the objective of the current analysis is to incorporate multiple slip effects in the flow of micropolar nanofluids due to a shrinking surface. The velocity, thermal, and concentration slip effects are endorsed to analyze the flow. Insights into heat transfer are subject to the radiative phenomenon. The stability analysis of the defined problem has been performed. The developed problem into a dimensionless form is solved with the help of the Keller box scheme. The accuracy of solution is confirmed with available research data. The implementation of the Keller box technique leads to multiple solutions. Physical justification of the problem is presented for each flow parameter. It is observed that dual solutions exist for specific numerical values of involved parameters for the shrinking flow problem. A reduction in fluid velocity is noticed for the velocity slip parameter. The micro-rotational profile declined due to the micro-rotation parameter. Furthermore, heat transfer enhances due to Brownian and thermophoresis parameters.